A clinical case of performing risk-reducing surgery with simultaneous implant reconstruction with a mutation in the BRCA1 gene - E. M. Kungurtseva; D. A. Ryabchikov; N. V. Chanturiya; A. N. Khakimov; T. T. Khaidarov; E. S. Makarov; M. G. Filippova (Academy for Practical Oncology, 2026)
The article highlights the issue of the possibility of performing risk-reducing mastectomy as a cancer prevention for hereditary diseases. A review of the scientific literature has been conducted confirming the advantage of this operation. A clinical case of bilateral subcutaneous mastectomy with simultaneous implant reconstruction in the presence of a mutation in the BRCA1 gene is described.